Homo Economics: Capitalism, Community, and Lesbian and Gay Life - Pilon, Dennis (Labour / Le Travail, 1998)
The article reviews the book, "Homo Economics: Capitalism, Community, and Lesbian and Gay Life," edited by Amy Gluckman and Betsy Reed.